Pengaruh Company Size, Profitbility, Dan Inflation Terhadap Financial Distress (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
The purpose of this study was to analyze the effect of company size, profitability, and inflation on financial distress in manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2017-2019 period. This study uses 74 manufacturing companies that have been selected through a purposive sampling method with a total of 222 data for three years. The data used in this research are secondary data in the form of financial statements that end on December 31 in each period and also from BPS (Badan Pusat Statistik). Data processing in this study uses Eviews Student Version 11. The results showed that company size had negative and insignificant effect on financial distress, profitability had negative and significant effect on financial distress, and inflation had positive and insignificant effect on financial distress. The implication of this study